Acidente de trabalho entre a equipe assistencial multiprofissional: uma avaliação da subnotificação - Jacqueline de Almeida Goncalves (2007)
It was a cross-sectional epidemiological study, carried out at the Surgical Center of a general public university hospital, with teaching, research, and attending activities. The aim was to evaluate the notification of work accidents among the Health Multiprofissional Team of the Surgical Center unit; to identify the incidence of the accidents with biological material; to determine the immunization situation for Hepatitis B among the professionals who suffer the accidents; and to seek the conditions that workers attribute the occurrence of the accident. The data were collected from March to June 2007 using a questionnaire, and the analysis was made using descriptive statistics, Qui-square and Fisher Exact tests. The 127 research participants were classified in the following categories: physicians (23,8%), medical residents (30,1%), nurses (1,6%), technicians (20,9%) and nursing assistants (16,5%), and general services workers (7,1%).The majority of physicians were man (82,4%); in the nursing team, there was a female prevalence (76%) and for general services, they were exclusively feminine. The professionals' average age was 34 years; and they also had, on average, ten years after graduation, eight years of labor at the hospital of the study, and seven years in the specific unit. According to the survey responses, the dispose of sharp-edged material was in an appropriate way for 81,1% and the non recapping needles happened in only 43,4%. Among the professionals, 48,8% did not know the meaning of the acronym WAC and 98,9% admit to have received information on biosafety in some moment of their formation or professional experience. The complete hepatitis B vaccine series was verified in 75,6% and the serological confirmation test (anti-Hbs) in 40,2% for the totality of the participants. The work accident was notified by only 15,4% of the respondents. The reasons for not notifying were the irrelevancy of the accident, lack of knowledge of the routine protocol, indifference and work overload. The professional category that experience more accidents was the physician (46,6%), followed by medical residents (33,3%), technicians and nursing assistants (13,4%) and the professionals of general services (3,3%). The immunization of the rough professionals was evidenced in 80%, with accomplishment of anti-Hbs in 56,7%. The main activities involved in the occurrence of the accidents were the needle handling (73,3%) and the surgical procedures (56,7%). The physician category had 6,3 (2,2-17,8) times more chance of suffering an accident and 3,8 (1,5-9,7) times more chance of that accident to happen among men. For the inadequate dispose of the sharp-edged material, the chance of accident was 3,4 (1,2-9,3) times. According to these results, it is suggested to implement professionals training on adoption of biosafety measures, through the accomplishment of programs of continuous education, conferences regarding flow of accidents notification, and the worker's legal support seeking to reduce accidents involving sharp-edged material.